Riqualificazione del Museo Dante a Ravenna in chiave tecnologica - Touchwindow (Archeomatica, 2022)
The Municipality of Ravenna has commissioned the total technological refitting of the exhibition rooms of the Dante Museum to the company Touchwindow, professionals in the creation, design, production, activation and management of highly interactive spaces. Touchwindow has made the different environments more attractive to visitors, completely revolutionizing the customer experience through immersive paths with audio-visual effects and software capable of conveying information in interactive mode.